Chronic thromboembolic pulmonary hypertension - Kim, Nick H; Delcroix, Marion; Jenkins, David P; Channick, Richard; Dartevelle, Philippe; Jansa, Pavel; Lang, Irene; Madani, Michael M; Ogino, Hitoshi; Pengo, Vittorio; Mayer, Eckhard (Journal of the American College of Cardiology, 2013)
Since the last World Symposium on Pulmonary Hypertension in 2008, we have witnessed numerous and exciting developments in chronic thromboembolic pulmonary hypertension (CTEPH). Emerging clinical data and advances in technology have led to reinforcing and updated guidance on diagnostic approaches to pulmonary hypertension, guidelines that we hope will lead to better recognition and more timely diagnosis of CTEPH. We have new data on treatment practices across international boundaries as well as long-term outcomes for CTEPH patients treated with or without pulmonary endarterectomy. Furthermore, we have expanded data on alternative treatment options for select CTEPH patients, including data from multiple clinical trials of medical therapy, including 1 recent pivotal trial, and compelling case series of percutaneous pulmonary angioplasty. Lastly, we have garnered more experience, and on a larger international scale, with pulmonary endarterectomy, which is the treatment of choice for operable CTEPH. This report overviews and highlights these important interval developments as deliberated among our task force of CTEPH experts and presented at the 2013 World Symposium on Pulmonary Hypertension in Nice, France.
Keywords: RCTs; pulmonary hypertension; Humans; ventilation/perfusion; MRI; chronic thromboembolic pulmonary hypertension; PTPA; VQ; pulmonary artery pressure; Chronic Disease; PH; ACP; deep hypothermic circulatory arrest; CTPA; PEA; CTEPH; lidé; DHCA; PAH; Hypertension, Pulmonary; zvířata; plicní embolie; magnetic resonance imaging; pulmonary angiogram; CT; Pulmonary Embolism; ventilation/perfusion scan; antegrade cerebral perfusion; plicní hypertenze; extracorporeal membrane oxygenation; randomized controlled trials; chronická nemoc; ECMO; percutaneous transluminal pulmonary angioplasty; srdeční katetrizace; Cardiac Catheterization; pulmonary vascular resistance; PAP; Animals; computed tomography; computed tomography pulmonary angiogram; pulmonary arterial hypertension; pulmonary endarterectomy; PVR